Spatial Correlation Study of Covid-19 Incidents with Unemployment Rates in East Java Province - Nicken Ayu Andhika Mayangsari; Choirul Amin (Amcolabora, 2023)
The COVID-19 outbreak has hit many countries in the world, including Indonesia. The impact isextraordinary for the state order, one of which is in the economic sector. Starting from the problem ofthe economic crisis, so that in Indonesia there were also massive layof s as a result of the covid-19pandemic in which 90% of workers were laid of and 10% of workers were laid of . So this triggers anincrease in the unemployment rate in Indonesia. East Java Province also experienced an increase inthe unemployment rate in 2020. This study aims to analyze the spatial pattern of covid-19 andunemployment, as well as analyze the spatial correlation of covid-19 with unemployment in East JavaProvince using Moran Index analysis in the form of Univariate Moran's I and Bivariate Moran's I.The results of the analysis show that the spatial pattern of Covid-19 and unemployment in East JavaProvince are clustered. The results of the spatial correlation of covid-19 with unemployment show apositive value, which means that there is a spatial correlation between covid-19 and unemployment inthe city/regency of East Java Province. Where cities/districts that have a high number of COVID-19are surrounded by cities/districts with a high number of unemployed.